1981
DOI: 10.1111/j.1365-3091.1981.tb01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin and diagenetic evolution of Ca–Mg–Fe carbonates in some coalfields of Japan

Abstract: Carbonate concretions, lenses and bands in the Pleistocene, Palaeogene and Upper Triassic coalfields of Japan consist of various carbonate minerals with varied chemical compositions. Authigenic carbonates in freshwater sediments are siderite > calcite > ankerite > dolomite B ferroan magnesite; in brackish water to marine sediments in the coal measures, calcite > dolomite > ankerite > siderite + ferroan magnesite; and in the overlying marine deposits, calcite > dolomite %-siderite.Most carbonates were formed pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

1982
1982
1995
1995

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(44 citation statements)
references
References 27 publications
3
41
0
Order By: Relevance
“…The Utatsu berthierine, for example, is derived from sideritic rock in carbonaceous, kaolinitic shale of freshwater coalswamp deposits. This seems to reflect the fact that the siderite in these deposits is a low-Ca, low-Mg variety with nearly an end-member composition (Matsumoto, 1978;Matsumoto and Iijima, 1981). On the other hand, intermediate-to high-Mg berthierine is found in both modern and ancient, brackish water and shallow-marine sediments.…”
Section: Iijima and Matsumotomentioning
confidence: 99%
See 2 more Smart Citations
“…The Utatsu berthierine, for example, is derived from sideritic rock in carbonaceous, kaolinitic shale of freshwater coalswamp deposits. This seems to reflect the fact that the siderite in these deposits is a low-Ca, low-Mg variety with nearly an end-member composition (Matsumoto, 1978;Matsumoto and Iijima, 1981). On the other hand, intermediate-to high-Mg berthierine is found in both modern and ancient, brackish water and shallow-marine sediments.…”
Section: Iijima and Matsumotomentioning
confidence: 99%
“…The abundance of Fe 2+ in berthierine in the coal measures indicates that the reaction progressed under reducing conditions and in the presence of abundant plant remains. Most sideritic rocks in freshwater coal swamp deposits form at a burial depth less than 300 m during early diagenesis (Matsumoto, 1978;Matsumoto and Iijima, 1981). The siderite to berthierine transformation should, therefore, occur at greater depths.…”
Section: Iijima and Matsumotomentioning
confidence: 99%
See 1 more Smart Citation
“…7) is interpreted to reflect secondary growth of the coarser variety, probably involving partial recrystallisation of the spherulitic form. Matsumoto & Iijima (1981) suggested that there is a genetic relationship between kaolinite and siderite in coaly deposits, but did not fully explain how formation of minerals requiring apparently two different sets of chemical conditions occurred. We suggest that minor variation of pH alone, under reducing conditions, can explain the co-existence of these minerals.…”
Section: Sideritementioning
confidence: 99%
“…(1) at least a slightly alkaline pH (Garrels & Christ 1965;Todd & Monroe 1968;Pearson 1979), although it may be stable down topH 5.0 (Isphording & Lodding 1973); (2)negative Eh conditions (Todd & Monroe 1968;Isphording & Lodding 1973); (3) low dissolved sulphide, high dissolved carbonate (pCO 2 ), and high Fe 2+ activity (Garrels & Christ 1965;Curtis & Spears 1968;Isphording & Lodding 1973;Matsumoto & Iijima 1981;Tucker 1991). A nonmarine environment is the most common setting in which these conditions exist.…”
Section: Sideritementioning
confidence: 99%